CURATIVE BENEFIT OF SUBMUCOPERICHONDRIAL RESECTION OPERATION ON PULMONARY AR - Sheikh, Nadeem Ahmed; Choudhary, Azhar Ali; Nadeem, Kanwal; Khursheed, Areeba; Fatima, Rida; Shah, Syed Ausaf Ahmad (Pakistan Armed Forces Medical Journal, 2021)
Objective: We aimed at establishing a correlation between deviated nasal septum and pulmonary artery hypertension in patients reporting in Otorhinolaryngology (ENT) clinic at Combined Military Hospital Quetta, and evaluating the beneficial impact of sub mucoperichondrial resection (SMR) operation on right heart myocardial function, primarily related to Pulmonary Arterial Pressures of these patients of longstanding nasal septal deviation.Study Design: Descriptive; hospital-based cross-sectional survey.Place and Duration of Study: Departments of Otorhinolaryngology & Cardiology, Combined Military Hospital, Quetta, from Sep 2019 to Apr 2021.Methodology: Electrocardiographic and 2-Dimensional Echocardiographic parameters of 87 randomized patients suffering from symptomatic longstanding deviated nasal septum (DNS) who had consented to undergo sub mucoperichondrial resection (SMR) operation were compared and studied for any change in status of probability of pulmonary arterial hypertension before and two months after their surgery. Probability of pulmonary hypertension was estimated using probability criteria from updated European Society of Cardiology Pulmonary Hypertension Guidelines 2019. Patients were classified into low, intermediate and high probability depending upon the number of criteria fulfilled by echocardiographic parameters.Results: Two (2.3%) patients suffering from deviated nasal septum presented with p-pulmonale. Twelve (13.8%) reported with right bundle branch block, and 7 (8%) patients demonstrated right axis deviation on electrocardiography. Overall high probability to develop pulmonary hypertension was discovered in 2 (2.3%) patients. We observed a significant improvement in pulmonary artery pressures in patients suffering from long term upper airway obstruction, two months following sub mucoperichondrial resection operation, in terms of maximum velocity and peak tricuspid regurgitation, right ventricle/left..........